Effectiveness of Reagent-Grade and Food-Grade Citric Acid as Denture Cleanser in Reducing Candida albicans Colonies - Zulharistya Prima Sahda; An-Nissa Kusumadewi; Ista Meidarlina (Universitas Muhammadiyah Yogyakarta, 2025)
Candida albicans is an opportunistic pathogenic fungus commonly found in the oral cavity, with increased prevalence among denture wearers. Citric acid is known for its antimicrobial properties. Reagent-grade citric acid has been previously studied, while food-grade citric acid has not been investigated as a denture cleanser. This study, thus, aims to evaluate the effectiveness of reagent-grade and food-grade citric acid as denture cleansers in reducing Candida albicans colonies. The samples were heat-cured acrylic resin plates (n=28) contaminated with Candida albicans ATCC 10231 suspension, then soaked for 30 minutes in different solutions: reagent-grade and food-grade citric acid at concentration of 4%, 5%, 7%, and distilled water as negative control. Candida colonies on the plates were cultured, incubated, and counted using the Total Plate Count (TPC) method. Data were analyzed using Welch’s ANOVA followed by post-hoc T-test. As a result, the average number of Candida albicans colonies in the reagent-grade citric acid groups (4%, 5%, 7%) were (2.15, 1.75, 0.29) ×104 CFU/ml. In the food-grade citric acid groups (4%, 5%, 7%), the averages were (6.55, 4.27, and 3.17) × 104 CFU/ml. The distilled water group had the highest number of colonies (13×104 CFU/ml). The lowest reduction in colony count was in the 4% food-grade citric acid group (49.6%), while the highest reduction was in the 7% reagent-grade citric acid group (97.7%). Welch’s ANOVA indicated a significant difference (p<0.05) among all treatment groups. Reagent-grade and food-grade citric acid as acrylic denture cleansers are effective in reducing Candida albicans colonies.